(untitled) (The International Journal of Educational Sciences and Arts, 2023)
The main aim of this study was to investigate the most frequent L2 writing errors, which appeared at the sentence-level made by Libyan university students majoring in English. It also aimed at knowing the percentage of each type of error. Thirty (30) undergraduate Libyan students participated in this study. The methods used in this study were descriptive and analytic. The data were collected during the spring semester of 2018 through an essay writing. This study used Corder’s (1967) taxonomy of writing errors: grammatical, lexical, semantic, syntactic, and mechanics. This study was designed to answer the following questions: 1) what are the most types of errors made in English writing by EFL Libyan university students? 2) What are the reasons behind the most common types of writing errors among English language major students? 3) What are the suggested remedies to overcome writing problems made by English language major students? Different types of errors were identified. These errors could be due to overgeneralization in the target language, resulting from ignorance of rule restriction and incomplete application of rules and interference resulting from first language (Arabic) negative transfer. These findings were discussed with implications for English as foreign language Libyan teachers. Along with the discussion of findings, limitations of the present study were discussed, and suggestions for further research were highlighted.